Dirty Work, Dangerous Others: The Politics of Outsourced Immigration Enforcement in Mexico. Issue 1 (1st June 2020) - Vogt, Wendy
Abstract: While Mexico has been openly critical of US immigration enforcement policies, it has also served as a strategic partner in US efforts to externalize its immigration enforcement strategy. In 2016, Mexico returned twice as many Central Americans as did the United States, calling many to criticize Mexico for doing the United States' "dirty work." Based on ethnographic research and discourse analysis, this article unpacks and complicates the idea that Mexico is simply doing the "dirty work" of the United States. It examines how, through the construction of "dirty others"—as vectors of disease, criminals, smugglers, and workers—Central Americans come to embody "matter out of place, " thus threatening order, security, and the nation itself. Dirt and dirtiness, in both symbolic and material forms, emerge as crucial organizing factors in the politics of Central American transit migration, providing an important case study in the dynamics between transit and destination states.